The investment decision on generation Z in Capital Market - Hidayat, Chusnul Maulidina; Muntahanah, Siti (Junal Ilmu Manajemen, 2024)
Technological developments are felt in all fields, one of which is the economic sector. Technology is currently a necessity, especially for Gen Z. Starting from waking up until going to sleep, Gen Z always needs technology. Increasingly sophisticated technology provides many conveniences for Gen Z in activities, one of which is investing. Investment policies made by investors are supported by the ease of information they obtain from current technological developments. This research was conducted to determine the factors that influence investment interest in Gen Z. The methodology in this research is quantitative descriptive, in collecting data the author distributed questionnaires to all respondents. The results obtained from this research prove that financial literacy, risk perception and return expectations have a positive influence on Gen Z investment interest in the capital market.